PROMOTION OF PERSONAL HYGIENE IN CHILDREN: APPLICATION OF THE MAGUEREZ ARCH IN A UNIVERSITY EXTENSION PROJECT (CIPEEX, 2025)
Personal hygiene plays a crucial role in preventing infections and diseases, especially among children, whose immune systems are still developing. This academic work reports on the implementation of health education activities carried out at a Child Education Center (CEI) in Anápolis, Goiás, using the Arco de Maguerez methodology. The Arco de Maguerez is a methodological approach that includes five stages: “observation of reality,” “key points,” “theorization,” “solution hypotheses,” and “application to reality.” The project began with observing the reality, where the team of students and the CEI representative identified issues related to the children’s hygiene, such as a lack of knowledge about hygiene practices and difficulties in communication between the CEI and the caregivers. The second stage involved identifying critical points, including the children’s limited knowledge about personal hygiene and the unsatisfactory quality of cleaning practices. In the theorization phase, theoretical references were researched to better understand the problems and underlying causes. It was found that hygiene education should start early, as developing hygiene habits is essential for children's health and should be periodically reinforced. For the solution hypotheses, the project focused on instructing children on personal hygiene practices through playful activities. The applied methodology included discussion circles, music, and painting, using materials that made learning more accessible and engaging for the children. The main challenge encountered was discussing intimate hygiene, which was addressed with the help of a children’s song and activities adapted to the age group. In the application to the reality stage, the action was suitable despite difficulties such as a lack of resources and the need to maintain the children's attention. The activities helped promote a deeper understanding of the importance of personal hygiene, with active participation from the children and positive feedback from CEI teachers. The use of playful resources facilitated learning and the practical application of hygiene instructions. The project demonstrated that health education, when applied creatively and adapted to the target audience's needs, can have a significant impact on forming healthy habits. The experience highlighted the importance of university extension projects both for students' training and for improving health practices in the community. It is hoped that the activities will continue to positively influence hygiene practices and that future projects will expand the reach and impact of educational actions.
Keywords: hygiene; health education; extension activities